Efektivitas Inovasi Desain dan Persepi Kualitas Produk Terhadap Keputusan Pembelian Tenun Ikat Sintang Dengan Kepercayaan Konsumen Sebagai Variabel Mediasi di Outlet Datiyu Gaia Mall - Viola kalista; Mursalin, Adi; Pratiwi, Windi (JURNAL MANAJEMEN MOTIVASI, 2026)
This study examines the role of design innovation and perceived product quality in influencing purchase decisions for Tenun Ikat Sintang, with consumer trust as a mediating variable at Datiyu Gaia Mall Outlet. The study aims to analyze the direct and indirect effects among these variables. A quantitative approach was used with purposive sampling involving 136 respondents, and data were analyzed using PLS-SEM with SmartPLS. The results show that design innovation and perceived product quality positively and significantly affect consumer trust and purchase decisions. Consumer trust also significantly mediates these relationships. These findings imply that product design innovation, quality improvement, and trust-building strategies are essential to strengthen consumer purchase decisions.